RAT'S INJURED SCIATIC NERVE RECOVERY AFTER TREATMENT USING ELECTROSURGICAL INSTRUMENTS IN WELDING REGIME - V. Likhodiievskyi; A. Korsak; Yu. Chaikovskyi; O. Kryvosheyeva; K. Lopatkina; V. Chernets (Bogomolets National Medical University, 2015)
Summary. Functional, morphological and immunohistochemical features of injured sciatic nerve distal stump after surgical treatment with electric surgical device that allows soft tissues welding by high frequency current were investigated. It was revealed that high frequency electrosurgical technology application compared with standard method of peripheral nerve injury operative treatment provides more full regeneration of injured sciatic nerve which was confirmed by higher sciatic nerve functional index both with more complete neurotisation of peripheral stump and increase in number of S100+ Shwann cells in the group of animals who underwent surgical treatment using new method.